2020
DOI: 10.1093/ofid/ofaa409
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Parenteral Antimicrobial Therapy With Ceftolozane/Tazobactam via Continuous Infusion for Multidrug-Resistant Pseudomonas aeruginosa Osteomyelitis

Abstract: We present a case of Pseudomonas aeruginosa osteomyelitis treated with surgery and antibiotic therapy with ceftolozane-tazobactam in continuous infusion at home using an elastomeric pump. We discuss the use of ceftolozane-tazobactam in continuous infusion administered at home as an effective alternative for the treatment of multidrug-resistant Pseudomonas aeruginosa osteomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Real-world evidence concerning the use of ceftolozane-tazobactam in prolonged infusion are summarized in Table 2. Overall, one prospective study, one Monte Carlo simulation study, three retrospective studies, and four case reports [36 ▪▪ ,37,38 ▪▪ ,39–44] compared prolonged with intermittent infusion of ceftolozane-tazobactam or reported real-world experiences of ceftolozane-tazobactam prolonged infusion in the management of MDR P. aeruginosa infections (including pneumonia, bloodstream infections, complicated urinary or intrabdominal infections, bone or joint infections, meningitis, or skin and soft tissue infections). Pilmis et al [36 ▪▪ ] prospectively assessed 72 patients treated with ceftolozane-tazobactam for MDR P. aeruginosa infections (26.3% MIC ≥4 mg/L; 66.7% pneumonia), of whom 79% was admitted to intensive care unit (ICU), and more than half were immunocompromised.…”
Section: Introductionmentioning
confidence: 99%
“…Real-world evidence concerning the use of ceftolozane-tazobactam in prolonged infusion are summarized in Table 2. Overall, one prospective study, one Monte Carlo simulation study, three retrospective studies, and four case reports [36 ▪▪ ,37,38 ▪▪ ,39–44] compared prolonged with intermittent infusion of ceftolozane-tazobactam or reported real-world experiences of ceftolozane-tazobactam prolonged infusion in the management of MDR P. aeruginosa infections (including pneumonia, bloodstream infections, complicated urinary or intrabdominal infections, bone or joint infections, meningitis, or skin and soft tissue infections). Pilmis et al [36 ▪▪ ] prospectively assessed 72 patients treated with ceftolozane-tazobactam for MDR P. aeruginosa infections (26.3% MIC ≥4 mg/L; 66.7% pneumonia), of whom 79% was admitted to intensive care unit (ICU), and more than half were immunocompromised.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly useful in the nonacute health care setting, but to date, limited data exist on the utilization and outcome of C/T in this setting. The case reports described in the literature have shown successful outcomes with C/T in the outpatient setting primarily against MDR P. aeruginosa infections administered as continuous infusions [ 6 , 11 , 14 , 16 , 18 , 25 ]. Jones and colleagues reported symptomatic and microbiologic resolution in 6/7 and 3/3 patients, respectively, following continuous infusion of C/T for P. aeruginosa infections in the outpatient setting [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the treatments, including colistin and polymyxin B, precluded transition to outpatient therapy due to potential adverse events, especially nephrotoxicity [ 22–24 ]. In addition, real-world experience of C/T utilization and associated outcomes in the outpatient setting is limited to case studies [ 6 , 11 , 14 , 16 , 18 , 25 ]. Previous studies have reported successful outcomes following continuous infusion of C/T for P. aeruginosa infections in both inpatient and outpatient settings [ 11 , 14 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients have a history of having been recently hospitalized or being immunocompromised by diabetes mellitus ( 3 , 5 ). Otero et al described an 88-year-old woman with a history of obesity and type 2 diabetes mellitus who had acute osteomyelitis of the phalanx and metatarsal of the toe caused by P. aeruginosa soon after amputation of the fourth toe ( 2 ). As Otero et al noted, cases of osteomyelitis induced by P. aeruginosa in otherwise healthy adults are rare.…”
Section: Discussionmentioning
confidence: 99%